1992
DOI: 10.1190/1.1443228
|View full text |Cite
|
Sign up to set email alerts
|

Imaging and velocity estimation with depth‐focusing analysis

Abstract: Prestack depth migration uses two imaging conditions, zero time and zero offset, during downward continuation to form a migrated depth section. When the migration velocities are exact, the two imaging conditions act in a complementary fashion to yield a focused image. When the migration velocities are in error, reflected energy collapses to zero offset at depths that are inconsistent with the zero‐time imaging condition. The result is a deteriorated seismic image. However, by interpreting the nonzero times at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(52 citation statements)
references
References 0 publications
0
51
0
1
Order By: Relevance
“…The generalized imaging condition (Doherty & Claerbout, 1974;Yilmaz & Chambers, 1984;MacKay & Abma, 1992;Rickett & Sava, 2002;Sava & Fomel, 2006) allows a finite spatial and temporal shift between the wavefields. The correct velocity model will focus energy in the correlation at zero shift.…”
Section: Generalized Imaging Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The generalized imaging condition (Doherty & Claerbout, 1974;Yilmaz & Chambers, 1984;MacKay & Abma, 1992;Rickett & Sava, 2002;Sava & Fomel, 2006) allows a finite spatial and temporal shift between the wavefields. The correct velocity model will focus energy in the correlation at zero shift.…”
Section: Generalized Imaging Conditionsmentioning
confidence: 99%
“…The underlying principle of MVA has not changed, but the precise way in which way the amount of focusing of the image is measured and the migration algorithms themselves have evolved. A few well-known methods found in this class are Differential Semblance Optimization (DSO), proposed by Symes & Carazzone (1991), which uses flatness of image gathers as a measure, and methods based on a generalized imaging condition, proposed by Doherty & Claerbout (1974) and elaborated on by many others (Yilmaz & Chambers, 1984;Stork, 1992;MacKay & Abma, 1992;Rickett & Sava, 2002;Sava & Biondi, 2004;Sava & Fomel, 2006). These methods have been proven successful on data in which multiples are not too strong (Mulder & ten Kroode, 2002;Shen et al, 2003;Dussaud & Symes, 2005;Li & Symes, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In DFA. all three assumptions are used (MacKay and Abma, in 1992). In RCA, the assumptions vary with migration types.…”
Section: Liu and Bleistein \Elocity Analysismentioning
confidence: 99%
“…The traditional RTM image is obtained by extracting the zerolag section from the extended image volume according to the traditional imaging condition. The idea of introducing redundant coordinates in the image domain goes back to the 'survey-sinking' concept of Claerbout (1985), and many variants have been considered over the years (MacKay and Abma, 1992;Berkhout, 1997;Rickett and Sava, 2002;Sava and Fomel, 2006;de Hoop et al, 2006;Yang and Sava, 2010). Stolk and de Hoop (2006) showed that such extended image volumes -in contrast to image volumes obtained by data-binning procedures-are essentially artifactfree, even for complex models.…”
Section: Introductionmentioning
confidence: 99%